Programma: 6 november The Meditations; 7 november The Big Awakening; 8 november G. Love and Special Sauce, Bobby Sichran, The Bucks; 9 november The Figgs, Love Spit Love; 10 november Jet Black Joe
Programma: 6 november The Meditations; 7 november The Big Awakening; 8 november G. Love and Special Sauce, Bobby Sichran, The Bucks; 9 november The Figgs, Love Spit Love; 10 november Jet Black Joe.